State Court Power to Enjoin Federal Judicial Proceedings: Donovan v. City of Dallas Revisited - Alan D. Hornstein; P. Michael Nagle (Washington University Law Quarterly, 1982)
In this Article, we do not intend to suggest that a state court may enjoin federal court proceedings merely upon a showing of a lack of federal jurisdiction over the parties or the subject matter. The injunctive power is that of a court of equity. An applicant would be required not only to show that the federal court was devoid of power to hear the case, but also to demonstrate the existence of whatever state law might require to justify injunctive relief. Thus, the rather limited focus here is the demonstration that there is no federal constitutional ban on state court injunctions against federal proceedings, pending or impending, once a state equity court determines that the federal court lacks jurisdiction.
Keywords: Courts -- United States -- States; Federal jurisdiction; Injunctions